THE IMPACT OF COMPETENCIES, RISK MANAGEMENT AND AUDITORS INTERACTIONS ON INTERNAL AUDIT EFFECTIVENESS IN LIBYAN COMMERCIAL BANKS - Ashour, Mohamad Salah R.; Sukoharsono, Eko Ganis; Ghofar, Abdul (Accounting Department,, 2015)
Internal audit (IA) has become an important and integral function of organizations in achieving their objectives and protecting their assets. Nonetheless, IA effectiveness has received scant attention in the literature, especially in the context of developing countries such as Libya. The research aimed To analyze the impact of competencies of the internal audit team, risk management and interaction between internal auditors and audit committees on internal audit effectiveness in Libyan commercial banks. The research used the quantitative methodology for analysis.the sampling technique used in this research was random sampling. Participants in research included 105 auditors selected from branches of commercial banks in Libya. The research adopted the descriptive method using the survey from the commercial banks and its branches and analysing the impact of competencies, rick managment and auditors interection on internal audit effectivness. The results of this research showed that: firstly; Competencies of an Internal Audit team on Internal audit effectivenessÂ was significant and positive correlation. Secondly; Risk management on Internal audit effectiveness was higer significant and positive correlation. Thirdly; Interaction between IA and AC on Internal audit effectiveness was significant and positive correlation.Keywords: Competencies of Internal Audit team, Risk Management, Interaction between Internal Auditors and Audit Committees and Internal Audit Effectiveness.